Analisis Tindak Tutur Evaluatif Pada Teks Tanggapan Dalam Buku Bahasa Indonesia SMP Kelas IX Kurikulum 2013 - M. Andhika Pebrian; Muhammad Fahmi Nurhadi; Delia Eka Putri; Trinia Utami Dewi; Hana Minhatul Maula; Qurrota Ayu Neina; Asep Purwo Yudi Utomo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to analyze the types of evaluative speech acts in critical response texts in the Indonesian Middle School Class IX 2013 Curriculum book. The focus of this study is the five response texts contained in the presentation of material in the Indonesian Middle School Class IX 2013 Curriculum book on page 89, 90 to 92nd, 99th to 100th, 101st to 105th, and 107th to 113th. Read-carefully and note-taking techniques are the data collection techniques in this research. Meanwhile, the method used to approach this article is a qualitative descriptive and pragmatic approach. Data analysis processing in this research uses the method of matching. The results of the study include types of evaluative speech acts including, the first, Evaluative Speech Acts of Praising, the second, Evaluative Speech Acts of Criticism, the third, Evaluative Speech Acts of Praise, the fourth, Evaluative Speech Acts of Blaming, and the fifth, Evaluative Speech Acts of Correcting. Based on the analysis that has been carried out, it was found that there were 17 speech acts of praising, 7 speech acts of praise, 4 speech acts of criticism, 2 speech acts of blaming, and 1 speech act of correcting. The most widely used speech act is the speech act of praise.